Degradable bio-based material with structural color and preparation method thereof

By pressing the hybrid solution of hydroxylcellium cellulose, small molecular carboxylic acids and water at room temperature, suppress drying and forming, and prepare a degradable biological base material with structural and excellent mechanical properties. Insufficient performance and high energy consumption and serious pollution process have been realized, and green environmental protection and degradable materials are realized.

CN119350720APending Publication Date: 2025-01-24SHANDONG ZHONGKANG GUOCHUANG RES INST OF ADVANCED DYEING & FINISHING TECH CO LTD

Patent Information

Application Number
CN202411264734.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When existing bio-based photonic materials pursue excellent optical properties, their mechanical properties are insufficient, and the preparation process has problems such as high temperature, high pressure, large energy consumption and serious environmental pollution.

Method used

The hybrid solution of hydroxylcellin, small molecular carboxylic acid and water is suppressed to form a degradable bio -based material with structural color. This method is performed at room temperature to avoid the use of high temperature and high pressure, and improves the mechanical properties of the material through the addition of small molecular carboxylic acids.

Benefits of technology

The color of the material is adjusted, the mechanical properties are excellent (at least 60MPa), and the preparation process is green and environmentally friendly, the material can be degraded, and the requirements of sustainable development are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350720A_ABST
    Figure CN119350720A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable bio-based material with structural color and a preparation method thereof, and the preparation method comprises the following steps: uniformly mixing hydroxy propyl cellulose, small molecular carboxylic acid and water to obtain a mixed solution; and pressing, drying and forming the mixed solution to obtain the degradable bio-based material. The mass fraction of the hydroxy propyl cellulose in the mixed solution is 50-70 wt%. In the mixed solution, the mass fraction of the small molecular carboxylic acid is 10-16wt%. According to the degradable bio-based material with the structural color provided by the invention, the preparation process is green and environment-friendly, and the obtained degradable bio-based material is adjustable in color and has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional materials, and in particular to a degradable bio-based material with structural color and a preparation method thereof. Background Art

[0002] At present, petroleum-based plastics are often widely used in various fields due to their excellent stability and low price, such as food packaging, clothing industry, medical care and transportation. However, this is accompanied by the increasingly serious global plastic pollution problem. Bio-based plastics, as a substitute for petroleum-based plastics, are now widely used in people's daily lives. They have the advantages of excellent renewability, low carbon emissions, and degradability, which can effectively solve the thorny problems brought by petroleum-based plastics.

[0003] The application of plastics is often inseparable from rich colors. Traditional dyeing methods, such as adding dyes or pigments to plastics, can give plastics different colors to improve practicality, but it also brings many troubles. Specifically, there are complex dyeing processes and pollution problems caused by dyeing. Therefore, it is of great significance to develop a biodegradable bio-based plastic that does not rely on the dyeing process.

[0004] The reason why photonic crystals produce color is that the microscopic structure of the surface of the object interferes with, diffracts, and scatters light. They will not fade or be bleached easily, thus achieving the purpose of long-term stable use. Among them, cellulose is a widely available bio-based polymer. In a few plants, this fibril is found to be assembled into a spiral nanostructure, and its periodicity is equivalent to visible light, thus producing structural color. However, excessive attention is paid to the optical properties (i.e., color) of cellulose-based photonic materials, and their mechanical properties are often ignored. Poor mechanical properties are a huge challenge to subsequent applications; in addition, the preparation process of most photonic crystals involves high temperature and high pressure, and the introduction of monomers with poor biocompatibility results in great energy consumption and environmental pollution. Therefore, it is of great significance to develop a method for preparing green and environmentally friendly bio-based degradable materials. Summary of the invention

[0005] Based on this, a method for preparing a degradable bio-based material with structural color is provided. The preparation process is green and environmentally friendly, and the obtained degradable bio-based material has adjustable color and excellent mechanical properties.

[0006] A method for preparing a degradable bio-based material with structural color, comprising the following steps:

[0007] Mixing hydroxypropyl cellulose, small molecule carboxylic acid and water uniformly to obtain a mixed solution;

[0008] The mixed solution is pressed, dried and formed to obtain the degradable bio-based material.

[0009] The present application provides a method for preparing a degradable biofilm having structural color and mechanical properties. The process is simple and environmentally friendly and can be obtained by simple room temperature drying.

[0010] The degradable bio-based material presents various colors within the visible spectrum. By adjusting the type and concentration of small molecule carboxylic acid, the degradable bio-based material can present different colors, and after drying and forming, it can still maintain a bright structural color.

[0011] The addition of small molecule carboxylic acids enables the degradable bio-based materials to retain structural color after drying and molding. At the same time, small molecule carboxylic acids form hydrogen bonds with the hydroxyl groups and ether bonds in hydroxypropyl cellulose, which plays a physical cross-linking role, making the degradable bio-based materials exhibit excellent mechanical properties. The breaking strength is at least above 60MPa, which is comparable to common plastic products.

[0012] In addition, the biodegradable bio-based material uses hydroxypropyl cellulose as raw material and is easy to recycle. When the product's service life ends, add an appropriate amount of water and mechanically mix to form a uniform hydroxypropyl cellulose-small molecule carboxylic acid slurry. Add carboxylic acid or hydroxypropyl cellulose into it and it can be prepared into a biodegradable bio-based material for use again. The raw material recycling rate is close to 100%.

[0013] The biodegradable bio-based material prepared in the present application can retain rich and bright colors while taking into account the mechanical properties of the material, and at the same time has good biodegradability. It comes from nature and finally returns to nature, forming a perfect closed loop, which provides the possibility of replacing petroleum-based plastics and moving towards a sustainable path.

[0014] Several optional methods are also provided below, but they are not intended to be additional limitations on the above-mentioned overall solution, but are merely further supplements or preferences. Under the premise that there are no technical or logical contradictions, each optional method can be combined with the above-mentioned overall solution separately, and multiple optional methods can also be combined.

[0015] The biodegradable bio-based material uses hydroxypropyl cellulose as the main raw material, and adds a small amount of small molecule carboxylic acid to adjust the color and as a physical cross-linking agent to improve the mechanical properties. The amount of small molecule carboxylic acid added should be appropriate. Too much or too little will reduce the mechanical properties.

[0016] Optionally, in the mixed solution, the mass fraction of hydroxypropyl cellulose is 50-70wt%.

[0017] Optionally, in the mixed solution, the mass fraction of the small molecule carboxylic acid is 10 to 16 wt %.

[0018] Optionally, in the mixed solution, the mass fraction of hydroxypropyl cellulose is 60 wt %, and the mass fraction of the small molecule carboxylic acid is 10-16 wt %.

[0019] Different types of small molecule carboxylic acids will affect the color of the degradable bio-based material. Optionally, the small molecule carboxylic acid is one of citric acid, L-malic acid, DL-malic acid, D-malic acid, lactic acid, tartaric acid, and butanetetracarboxylic acid.

[0020] Optionally, before the mixed solution is pressed and dried to form, bubbles are eliminated by high-speed centrifugation, the centrifugal speed is greater than 8000 r / min, and the centrifugal time is greater than 30 min.

[0021] In order to mix evenly, the mixed solution is first added to the defoaming box, mixed with a mixer for 40 to 80 minutes (for example, 60 minutes), and then the bubbles are eliminated by high-speed centrifugation. The centrifugal speed of the high-speed centrifugation is 8000 to 10000 r / min, and the centrifugal time is 30 to 60 minutes.

[0022] Optionally, the drying is performed at room temperature. The drying process of the preparation method provided in the present application can be performed at room temperature, where room temperature means that the temperature is not controlled by auxiliary equipment, and the room temperature is usually 10-40°C.

[0023] The present application also provides a degradable bio-based material with structural color, which is prepared using the degradable bio-based material.

[0024] Optionally, the breaking strength of the degradable bio-based material is not less than 60 MPa.

[0025] Optionally, the color of the degradable bio-based material is one of blue, green, yellow-green, orange, red, and blue-green.

[0026] The degradable bio-based material with structural color provided in the present application has a green and environmentally friendly preparation process, and the obtained degradable bio-based material has adjustable color and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The UV-reflectance spectrum of the degradable bio-based material prepared in Example 1;

[0028] Figure 2 The tensile curve of the degradable bio-based material prepared in Example 1;

[0029] Figure 3 The UV-reflectance spectrum of the degradable bio-based material prepared in Example 9;

[0030] Figure 4 This is the tensile curve of the degradable bio-based material prepared in Example 9;

[0031] Figure 5 A photograph of the degradable bio-based material prepared in Example 1;

[0032] Figure 6 A photograph of the degradable bio-based material prepared in Example 2;

[0033] Figure 7 A photograph of the degradable bio-based material prepared in Example 3;

[0034] Figure 8 A photograph of the degradable bio-based material prepared in Example 4;

[0035] Fig. 9 This is a photograph of the degradable bio-based material prepared in Example 5. DETAILED DESCRIPTION

[0036] The following further illustrates in detail through a plurality of examples that the present invention prepares a degradable bio-based film having both bright structural color and excellent mechanical properties through a room temperature drying strategy. The following examples are only provided for explanation and are not intended to limit the present invention.

[0037] Example 1

[0038] 6.0g hydroxypropyl cellulose (viscosity 3-6mPa.s at 20°C), 1.2g anhydrous citric acid, and 2.8g deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50mL centrifuge tube and centrifuged at a speed of 10,000r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily removed; after removing the release film, the sample was placed in a dryer to dry, and a blue degradable bio-based material was obtained. For photos of the degradable bio-based material prepared in this embodiment, see Figure 5 shown.

[0039] See also Figure 1 As shown, the reflection wavelength corresponding to the degradable bio-based material prepared in this embodiment is 480nm, which is consistent with the wavelength range corresponding to blue.

[0040] See also Figure 2 As shown, the biodegradable bio-based material prepared in this embodiment has excellent mechanical properties and a breaking strength of up to 70 MPa.

[0041] Example 2

[0042] 6.0g hydroxypropyl cellulose (viscosity 3-6mPa.s at 20°C), 1.3g anhydrous citric acid, and 2.7g deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50mL centrifuge tube and centrifuged at a speed of 10,000r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily removed; after removing the release film, the sample was placed in a dryer to dry, and a green, degradable bio-based material was obtained. For photos of the degradable bio-based material prepared in this embodiment, see Figure 6 shown.

[0043] Example 3

[0044] 6.0g hydroxypropyl cellulose (viscosity 3-6mPa.s at 20°C), 1.4g anhydrous citric acid, and 2.6g deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50mL centrifuge tube, and centrifuged at a speed of 10000r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily removed; after removing the release film, the sample was placed in a dryer to dry, and a yellow-green degradable bio-based material was obtained. For photos of the degradable bio-based material prepared in this embodiment, see Figure 7 shown.

[0045] Example 4

[0046] 6.0g hydroxypropyl cellulose (viscosity 3-6mPa.s at 20°C), 1.5g anhydrous citric acid, and 2.5g deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50mL centrifuge tube and centrifuged at a speed of 10,000r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily removed; after removing the release film, the sample was placed in a dryer to dry, and an orange degradable bio-based material was obtained. For photos of the degradable bio-based material prepared in this embodiment, see Figure 8 shown.

[0047] Example 5

[0048] 6.0g hydroxypropyl cellulose (viscosity 3-6mPa.s at 20°C), 1.6g anhydrous citric acid, and 2.4g deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50mL centrifuge tube, and centrifuged at a speed of 10000r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily removed; after removing the release film, the sample was placed in a dryer to dry, and a red degradable bio-based material was obtained. For photos of the degradable bio-based material prepared in this embodiment, see Fig. 9 shown.

[0049] Example 6

[0050] 6.0 g of hydroxypropyl cellulose (viscosity of 3-6 mPa.s at 20°C), 1.2 g of L-malic acid, and 2.8 g of deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50 mL centrifuge tube, and high-speed centrifuged at a speed of 10,000 r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily peeled off; after peeling off the release film, the sample was placed in a dryer to dry, and a blue degradable bio-based material was obtained.

[0051] Example 7

[0052] 6.0 g of hydroxypropyl cellulose (viscosity of 3-6 mPa.s at 20°C), 1.3 g of L-malic acid, and 2.7 g of deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50 mL centrifuge tube, and high-speed centrifuged at a speed of 10,000 r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily peeled off; after peeling off the release film, the sample was placed in a dryer to dry, and a blue-green degradable bio-based material was obtained.

[0053] Example 8

[0054] 6.0 g of hydroxypropyl cellulose (viscosity of 3-6 mPa.s at 20°C), 1.4 g of L-malic acid, and 2.6 g of deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50 mL centrifuge tube, and high-speed centrifuged at a speed of 10,000 r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily peeled off; after peeling off the release film, the sample was placed in a dryer to dry, and a yellow-green degradable bio-based material was obtained.

[0055] Example 9

[0056] 6.0 g of hydroxypropyl cellulose (viscosity of 3-6 mPa.s at 20° C.), 1.5 g of L-malic acid, and 2.5 g of deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50 mL centrifuge tube, and high-speed centrifuged at a speed of 10,000 r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily peeled off; after peeling off the release film, the sample was placed in a dryer to dry, and an orange degradable bio-based material was obtained.

[0057] See also Figure 3As shown, the reflection wavelength corresponding to the degradable bio-based material prepared in this embodiment is 595 nm, which is consistent with the wavelength range corresponding to orange.

[0058] See also Figure 4 As shown, the biodegradable bio-based material prepared in this embodiment has excellent mechanical properties and a breaking strength of up to 60 MPa.

[0059] Example 10

[0060] 6.0 g of hydroxypropyl cellulose (viscosity of 3-6 mPa.s at 20° C.), 1.6 g of L-malic acid, and 2.4 g of deionized water were weighed and added to a defoaming box, and mixed for 60 minutes in the "mix" mode of a mixer (ThinkyARE-310 planetary centrifugal mixer); after the mixing was completed, the mixture in the defoaming box was transferred to a 50 mL centrifuge tube, and high-speed centrifuged at a speed of 10,000 r / min for 45 minutes to eliminate bubbles; the above-mentioned uniform slurry obtained after centrifugation was transferred between two plates, separated by a "U-shaped" gasket in the middle, and protected on both sides of the gasket with a release film. After pressing for 1 hour, the pressed sample was immersed in liquid nitrogen so that the release film could be easily peeled off; after peeling off the release film, the sample was placed in a dryer to dry, and a red degradable bio-based material was obtained.

[0061] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0062] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a degradable bio-based material with structural color, characterized in that: The steps include: Mixing hydroxypropyl cellulose, small molecule carboxylic acid and water uniformly to obtain a mixed solution; The mixed solution is pressed, dried and formed to obtain the degradable bio-based material.

2. The method for preparing a degradable bio-based material with structural color according to claim 1, characterized in that: In the mixed solution, the mass fraction of hydroxypropyl cellulose is 50-70wt%.

3. The method for preparing a degradable bio-based material with structural color according to claim 1, characterized in that: In the mixed solution, the mass fraction of the small molecule carboxylic acid is 10-16 wt %.

4. The method for preparing a degradable bio-based material with structural color according to claim 1, characterized in that: In the mixed solution, the mass fraction of hydroxypropyl cellulose is 60 wt %, and the mass fraction of small molecule carboxylic acid is 10-16 wt %.

5. The method for preparing a degradable bio-based material with structural color according to claim 1, characterized in that: The small molecule carboxylic acid is one of citric acid, L-malic acid, DL-malic acid, D-malic acid, lactic acid, tartaric acid, and butanetetracarboxylic acid.

6. The method for preparing a degradable bio-based material with structural color according to claim 1, characterized in that: Before the mixed solution is pressed and dried to form, bubbles are eliminated by high-speed centrifugation, the centrifugal speed is greater than 8000 r / min, and the centrifugal time is greater than 30 min.

7. The method for preparing a degradable bio-based material with structural color according to claim 1, characterized in that: The drying was carried out at room temperature.

8. A biodegradable bio-based material with structural color, characterized in that: The method is prepared by using the degradable bio-based material as described in any one of claims 1 to 7.

9. The degradable bio-based material with structural color according to claim 8, characterized in that: The breaking strength of the degradable bio-based material is not less than 60 MPa.

10. The degradable bio-based material with structural color according to claim 8, characterized in that: The color of the degradable bio-based material is one of blue, green, yellow-green, orange, red, and blue-green.

Citation Information

Patent Citations

  • Coloring with cholesteric liquid crystal and its colored article

    JP2000226580A

  • Cholesteric polymer liquid crystal-forming composition and cholesteric polymer liquid crystal

    JP2000226581A

Cited By

  • Degradable bio-based material with structural color and preparation method thereof

    CN120795585A

  • Food colorant-enhanced HPC photonic gels, food colorant-enhanced HPC photonic gel films, and preparation thereof

    CN121699255A